Benefits of Resveratrol Supplementation - Fernandez-Quintela, Alfredo (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
In recent years, great attention has been paid to polyphenols due to their positive effects on health. One of the most widely-studied phenolic compounds is resveratrol. This molecule, which is naturally present in some foods, shows beneficial effects on various physiological and biochemical processes, thus representing a potential tool for the prevention or the treatment of diseases highly prevalent in our society. Several of these beneficial effects have been observed in human beings, but others only in pre-clinical studies so far, and therefore, it is mandatory to continue with the scientific research in this field. Indeed, new knowledge concerning these issues could enable the development of novel functional foods or nutraceuticals, incorporating resveratrol, suitable for preventing or treating diseases such as cancer, cardiovascular diseases, obesity, dislipemia, insulin resistance and diabetes, liver diseases, etc.